Numerical study of changes in tissue optical properties before and after the administration of nanoparticles. - Wong, Sun Leng. (2012)
Computer simulations have been frequently used in areas of research since guidelines for a real experiment could be obtained by from it, thereby saving both time and money. In this project, Comsol Multiphysics (COMSOL) was used to investigate the optical properties of nanoparticles of different sizes. In COMSOL, after entering various parameters and expressions, the scattering and absorption cross-sections of various sizes nanospheres can be simulated. Slight modifications are made to nanoparticles of different sizes to cater to simulations limitations, i.e., size of computer ram. These values will then be used to find out the scattering and absorption coefficients of nanoparticles at different wavelengths.